Eptesicus nilssoni ... - Honacki, James H.; Kinman, Kenneth E.; Koeppl, James W. (Zenodo, 1982)
Eptesicus nilssoni (Keyserling and Blasius, 1839). Arch. Naturgesch., 5(1):315. REVIEWED BY: W. B. Davis (WBD); E. Vernier (EV). TYPE LOCALITY: Sweden. DISTRIBUTION: W. and E. Europe to E. Siberia, and N.W. China (SW); north beyond Arctic Circle in Scandinavia, south to Iraq, the Elburz Mts., Pamirs and W. China (not Tibet (SW)); Nepal; Honshu, Hokkaido (Japan); Sakhalin. COMMENT: Includes propinquus; see Davis, 1965, J. Mammal., 46:230. Includes japonensis; see Corbet, 1978:57. Revised by Wallin, 1969, Zool. Bidr. Upps., 37:223-440. ISIS NUMBER: 5301405014004021001. ... : Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Chiroptera, pp. 111-215 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 175, DOI: 10.5281/zenodo.7352990 ...